Law Enforcement Against Motorcyckers Who Do Not Have a Driving License in Sukabumi Based on Undang-Undang no. 22 of 2009 - Maya, Nur Maya Raisa; Putri, R. Eriska Ginalita Dwi (International Journal of Law Analytics, 2024)
Motorized vehicles are currently one of the means of transportation used by Indonesian people. With the large number of motorbikes used, there are also many traffic violations occurring on the roads. Therefore, the government issued statutory regulations for road users, namely Law Number 22 of 2009. In this provision, motorbike users must have a driving license, which is stated in Article 77 paragraph (1) of the LLAJ Law. The fact is that there are still people who are still disobedient and do not have a driving license. Actions given to violators are carried out by repressive law enforcement, giving punishments in the form of tickets and fines given by law enforcers, sometimes not based on Article 281 of the LLAJ Law. This research aims to find out how law enforcement and the sanctions given are by those stated in the LLAJ Law. The method used is a qualitative method with an empirical juridical approach.